2017
DOI: 10.3897/subtbiol.24.15013
|View full text |Cite
|
Sign up to set email alerts
|

Evolution of coprophagy and nutrient absorption in a Cave Salamander

Abstract: The transition from carnivory to omnivory is poorly understood. The ability to feed at more than one trophic level theoretically increases an animal's fitness in a novel environment. Because of the absence of light and photosynthesis, most subterranean ecosystems are characterized by very few trophic levels, such that food scarcity is a challenge in many subterranean habitats. One strategy against starvation is to expand diet breadth. Grotto Salamanders (Eurycea spelaea (Stejneger, 1892)) are known to ingest b… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 26 publications
0
3
0
Order By: Relevance
“…The sole exception that regularly undergoes full metamorphosis in caves is the grotto salamander Eurycea spelaea . Members of this species exhibit an omnivorous diet (Soares et al 2017 ) and sometimes live in association with bat colonies, where they can feed on the dense invertebrate fauna and even on the nutrient-rich bat guano itself (Fenolio et al 2014 ). On the other hand, Proteus has inherited its aquatic and darkness-loving habits from surface ancestors.…”
Section: Why Are There So Few Cave-obligate Tetrapods?mentioning
confidence: 99%
“…The sole exception that regularly undergoes full metamorphosis in caves is the grotto salamander Eurycea spelaea . Members of this species exhibit an omnivorous diet (Soares et al 2017 ) and sometimes live in association with bat colonies, where they can feed on the dense invertebrate fauna and even on the nutrient-rich bat guano itself (Fenolio et al 2014 ). On the other hand, Proteus has inherited its aquatic and darkness-loving habits from surface ancestors.…”
Section: Why Are There So Few Cave-obligate Tetrapods?mentioning
confidence: 99%
“…Interestingly enough, this species of opilion is preyed upon inside the cave by insects and spiders [32]. Another example is that of cave salamanders that utilize resources from both the cave and the epigean environment [33]. According to numerous reports, snakes regularly predate on bats in tropical and subtropical caves [34][35][36].…”
Section: Feedbacksmentioning
confidence: 99%
“…Several amphibian species are known to regularly exploit subterranean environments but, besides numerous reports concerning several salamanders species (Niemiller and Miller 2007, Pierce et al 2014, Soares et al 2017, Vörös et al 2017, only a few species of frogs and toads (Anura) are known to exploit these environments (Fenolio et al 2005, Köhler et al 2010, Lunghi et al 2014, Koller 2017. Frogs have been usually considered as an accidental presence in subterranean environments (Bressi and Dolce 1999), but recently many authors showed that some Anuran species can be quite common in these sites, selecting caves with specific environmental features (Köhler et al 2010, Rosa and Penado 2013, Biswas 2014, Lunghi et al 2014, Matavelli et al 2015.…”
Section: Introductionmentioning
confidence: 99%